1984
DOI: 10.1126/science.6505694
|View full text |Cite
|
Sign up to set email alerts
|

Activated Expression of the N- myc Gene in Human Neuroblastomas and Related Tumors

Abstract: In neuroblastoma lines in which the N-myc gene is present as a single copy, the expression of N-myc as messenger RNA is increased relative to that in nonneuroblastoma cell lines and tumors. The increase of expression in neuroblastomas with amplified N-myc genes is the result of (i) an increase in the absolute amount of expression of each N-myc gene and (ii) an increase in the copy number of the N-myc gene. A second gene--which is amplified in many of the same lines as N-myc--is expressed to about the same degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
130
1
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(134 citation statements)
references
References 13 publications
2
130
1
1
Order By: Relevance
“…Oncogene N-MYC is often amplified in aggressive and undifferentiated neuroblastomas and its expression correlates with advanced disease. [26][27][28] Analysis of N-MYC amplification in neuroblastoma patients showed that CYLD expression was significantly lower in N-MYC-amplified compared with N-MYC-non-amplified neuroblastomas (Figure 1d). We could not find any correlation of CYLD expression with the different cellular phenotypic variants of neuroblastoma cell lines, including neuroblastic (N-type; SK-N-F1, SK-N-RA, SH-SY5Y and IMR-32) or more malignant neuroblastoma cells, the intermediate type (I-type; SK-N-BE(2)C and LA-N-2).…”
Section: Cyld Expression Is Associated With Clinical Outcomes In Neurmentioning
confidence: 99%
“…Oncogene N-MYC is often amplified in aggressive and undifferentiated neuroblastomas and its expression correlates with advanced disease. [26][27][28] Analysis of N-MYC amplification in neuroblastoma patients showed that CYLD expression was significantly lower in N-MYC-amplified compared with N-MYC-non-amplified neuroblastomas (Figure 1d). We could not find any correlation of CYLD expression with the different cellular phenotypic variants of neuroblastoma cell lines, including neuroblastic (N-type; SK-N-F1, SK-N-RA, SH-SY5Y and IMR-32) or more malignant neuroblastoma cells, the intermediate type (I-type; SK-N-BE(2)C and LA-N-2).…”
Section: Cyld Expression Is Associated With Clinical Outcomes In Neurmentioning
confidence: 99%
“…We reported previously that eight independent human small-cell lung cancer (SCLC) lines have stable amplification and increased expression or deregulated expression alone of the c-myc gene (6,10). Recent studies have shown increased expression with or without amplification of a c-myc-related gene, N-myc, in tumors of neural origin, including neuroblastoma and retinoblastoma (7)(8)(9). In this paper, we show that six independently derived SCLC lines that express neuroendocrine properties (10)(11)(12) also have amplified Nmyc sequences and increased levels of N-myc expression compared to non-N-myc-amplified cell lines.…”
mentioning
confidence: 79%
“…In the SCLC cell lines examined to date, we have found no cell lines to have the c-myc, N-myc, or L-myc genes simultaneously amplified or expressed. DISCUSSION N-myc amplification and/or expression is observed thus far in three human tumors, all of which have neural or neuroendocrine properties: neuroblastoma (7,8), retinoblastoma neuroblastoma is associated with a more advanced clinical stage (4). In neuroblastoma (7,8,30) and SCLC, the amplification is a somatic event present in tumor but not in normal tissue from the same patient.…”
Section: N-myc Dna Ampliflication Is Stable Over Time In Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon di erentiation to the mature B cell stage, coincident with completion of immunoglobulin (Ig) gene expression, N-myc expression turns o and remains o (Reth et al, 1985;Zimmerman et al, 1986;Smith et al, 1992;Morrow et al, 1992). The oncogenic potential of the human N-myc gene has been implicated in various tumors including neuroblastoma (Brodeur et al, 1984;Kohl et al, 1984), Wilms' tumor (Nisen et al, 1986), retinoblastoma (Lee et al, 1984), small cell lung carcinoma , medullary thyroid carcinoma (Roncalli et al, 1994), testis (Shuin et al, 1994), brain (Hirvonen et al, 1994), and breast (Mizukami et al, 1995). Human N-myc gene expression has been observed to be elevated in several AML and ALL leukemias and leukemic cell lines (Hirvonen et al, 1991) while not detectable in pre-preB and preB leukemic cell lines (Wetherall and Vogler, 1992).…”
Section: Introductionmentioning
confidence: 99%